(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
To evaluate the serologic (IgG) response to Helicobacter pylori in asymptomatic population, a total of 45 asymptomatic healthy adults aged 18-65 years were included in the study. The study was carried out in the department of Microbiology, Mymensingh Medical College between July, 2006 to June, 2007. The sera samples of the participants were tested for presence of anti-H. pylori IgG by using Enzyme Linked Immunosorbent Assay (ELISA). Seropositivity rate for anti-H. pylori IgG in asymptomatic adults was found 88.89% at a cut-off level of 5 arbU/ml. The impact of changing cut-off level for IgG seropositivity was also examined in the present study. The seropositivity rate for anti-H. pylori IgG at 10 arbU/ml was found 71.11%. Bangladesh J Med Microbiol 2008; 02 (02): 31-34